Comprehensive Review of Dietary Supplements Used by Athletes: Types and Benefits - Adrian Uchto; Sara Gierczak; Kacper Zając; Michał Dróżdż; Julia Wójcik; Kacper Wojciech Pamuła; Karolina Palacz (Nicolaus Copernicus University in Toruń, 2024)
Introduction. A dietary supplement is intended to improve nutrition by providing vitamins, minerals, herbs, or amino acids. These supplements are taken orally, labeled as supplements, and are not meant to be a substitute for regular food. The increasing interest in strength training and fitness emphasizes the significance of proper nutrition. Engaging in physical activity reduces the risk of disease and enhances mental health. More research is required to understand the impact of supplements on performance, health, and the gut microbiome. Aim of study. The primary objective of this research is to compile existing data on dietary supplements commonly utilized in sports, including but not limited to creatine, protein, branched-chain amino acids, omega-3 fatty acids, and L-citrulline. Materials and methods. 50 articles pertaining to the issue were subjected to analysis. These articles were sourced from PubMed and Google Scholar, spanning a publication period of 19 years. Conclusions. Creatine supplementation consistently enhances strength, endurance, and lean mass, particularly when combined with resistance and plyometric training, although its impact on fat mass is modest. Whey protein effectively promotes muscle mass and strength, especially in older adults, and aids in recovery from exercise-induced muscle damage. Branched-Chain Amino Acids can reduce muscle soreness and assist in recovery, but their effects on performance and muscle damage are less pronounced. Omega-3 fatty acids improve muscle recovery and metabolic markers, but exhibit limited synergy with resistance training. L-citrulline elevates arginine levels and improves vascular function, yet its effects on performance are minimal in certain contexts.